2018
DOI: 10.1093/jhps/hny043
|View full text |Cite
|
Sign up to set email alerts
|

Injectable autologous chondrocyte implantation (ACI) in acetabular cartilage defects—three-year results

Abstract: To evaluate the clinical outcome after arthroscopic matrix-associated injectable autologous chondrocyte implantation (ACI) in patients with large full-thickness acetabular cartilage defects. ACI was performed in young patients with full-thickness acetabular cartilage defects ≥2 cm2 in a two-step arthroscopic procedure. The patients were followed closely with clinical examinations and pre- and postoperative scores. The modified Harris Hip Score (mHHS), iHOT33 questionnaire (iHOT33) and the Subjective Hip Value … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…The search included 10 studies 11 , 12 , 14 , 15 , 19 , 20 , 29 , 33 , 34 , 36 that fulfilled the inclusion criteria: 2 randomized controlled trials, 15 , 19 7 case series, 11 , 12 , 19 , 20 , 33 , 34 , 36 and 1 cohort study. 14 Of the 10 studies, 6 studies addressed ACT3D of articular cartilage defects in the knee joint, 11 , 14 , 15 , 29 , 33 , 34 and 4 publications investigated the outcome of ACT3D therapy in affected hip joints.…”
Section: Resultsmentioning
confidence: 99%
“…The search included 10 studies 11 , 12 , 14 , 15 , 19 , 20 , 29 , 33 , 34 , 36 that fulfilled the inclusion criteria: 2 randomized controlled trials, 15 , 19 7 case series, 11 , 12 , 19 , 20 , 33 , 34 , 36 and 1 cohort study. 14 Of the 10 studies, 6 studies addressed ACT3D of articular cartilage defects in the knee joint, 11 , 14 , 15 , 29 , 33 , 34 and 4 publications investigated the outcome of ACT3D therapy in affected hip joints.…”
Section: Resultsmentioning
confidence: 99%
“…It reflects the perspective of the patient and is easily administered and time-saving for the patient and the investigator. Although the subjective hip value has been used to report on results after hip arthroscopy, cartilage implantation of the hip and muscular reconstructions of the hip abductors, it has never been evaluated before [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. We could show a high and statistically significant correlation between the subjective hip value and established hip measures such as the modified Harris hip score and the International Hip Outcome Tool.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of higher average scores in the modified Harris hip score compared to the subjective hip value was seen earlier, with the modified Harris hip score improving faster after hip arthroscopy compared to the International Hip Outcome Tool [ 44 ]. Higher scores were also seen after surgical dislocation of the hip, but no information was given if the Harris hip score was used in the modified or original version [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of 32 hips treated with chondrocytes embedded in injected gels with a 3-year followup concluded that this method was suitable for large defects in weight-bearing zones. [32] Collaboration between clinicians and tissue engineers is essential for the development of such innovations. A lack of literature investigating large groups of patients with long-term follow-up warrants further investigation into this technique.…”
Section: Management Of Articular Cartilage Injuriesmentioning
confidence: 99%